Deep submerged speleothems in the Sansha Yongle Blue Hole (South China Sea) as determination of low sea levels during the Last Glacial Maximum - Yu, Xiaoxiao; Duan, Baichuan; Zhao, Jingyao; Gu, Dongqi; Feng, Aiping; Liu, Yanxiong; Li, Tiegang (Frontiers in Marine Science, 2022)
Although Last Glacial Maximum (LGM) sea-levels have been the focus of much attention in climate and marine sciences, the timing, duration and magnitude need better constraints. Here we present observations and analyses of the deepest speleothems (-116 m) collected from the deepest known blue hole at the global scale, the Sansha Yongle Blue Hole (SYBH), Xisha Islands, South China Sea. The field investigations illustrate that submerged speleothems are irregular cauliflower-like coatings on the downward cave ceiling from water depths of 90 to 120 m. The downward growth direction and negative stable carbon and oxygen stable isotopes of submerged speleothems suggest that they may deposit in an air-filled condition through gravity drip, constraining the maximum LGM sea-level. Precious dating was conducted for these deep submerged speleothems with two U-Th ages of 29.16±0.17 and 26.04±0.18 ka BP and one radiocarbon age of 18.64 ± 0.12 ka BP, respectively. Our investigated deep submerged speleothems therefore clearly constrain the minimum onset and maximum termination times for the LGM in terms of sea-level. The results show that LGM initiated at 29 ka BP and ended at 18.5 ka BP. This study therefore provides the first evidence for the use of deep speleothems to constrain LGM sea-levels and emphasizes the importance of deep submerged speleothems in reconstruction of Pleistocene low sea-levels.